Between two fires - Villasin, Irene S. (Animo Repository, 1979)
Rogelio Buenaventura, a fourth year student, was dropped by the administrators and teachers due to the following violations of the schools regulation for many times like coming to school drunk, assaulting of teachers, threatening of teachers and administrators and vandalism. The principal could not make up her mind on what to do with the case. The threatening words of Mr. Buenaventura and the recommendations of the disciplinary committee were bothering her. What should she do? She would like to maintain the good reputation of the school as well as the good relationship with the community plus the standard of the school. At the same time she felt responsible for the son of Mr. Buenventura as she was the one who admitted him to school.